Comparative Study Forms of Element Artistic Talent Search Event in "RCTI's Indonesian Idol Junior and GTV's The Voice Kids Indonesia" Grand Final Episode Production Year 2018 - Faradina Dwi Novitasari (ROLLING, 2020)
In 2003, the competition event began its existence on Indonesian television. Singing competition event is one of the programs compete on Indonesian television until 2018. The television programs has an intense competition are Indonesian Idol Junior 2018 which broadcast on RCTI and The Voice Kids Indonesia 2018 which broadcast on GTV. Both of the programs show their best, especially in the artistic arrangement. Hence, the study will discuss the artistic elements in both of the singing competition programs and try to find out the similarities and differences of the artistic and aesthetic elements through the artistic arrangement. This comparative research uses qualitative descriptive methods to get the deepest and the meaningful data. The data collection includes observation by watching videos. This study aims to find out the kind of the similarities and differences of the elements in artistic order, include the stage setting, decoration, lighting, wardrobe, makeup and the aesthetics of Indonesian Idol Junior 2018 and The Voice Kids Indonesia 2018. Then, Jakob Sumardjo explains that aesthetic contains of 5 elements, these are object, subject, economy, politic or social institution, and context.The study results that both of the programs show many similarities and differences between all elements in the artistic used.